Biofuels spray and combustion characteristics in a new micro gas turbine combustion chamber design with internal exhaust recycling - Mohammed R. Abdulwahab; Khaled A. Al-attab; Irfan Anjum Badruddin; Muhammad Nasir Bashir; Joon Sang Lee (Case Studies in Thermal Engineering)
The characteristics of atomization and combustion of biodiesel and palm oil were evaluated in this study. A new combustor design with internal exhaust gas recycling (iEGR) and internal fuel pre-evaporation was investigated numerically and then verified experimentally using micro gas turbine (MGT) test rig. CFD evaluation of hydrodynamics flow of 8 iEGR mechanisms geometries showed that simple connection between the exhaust and recycle tube resulted in 0 % gas recycling due to the pressure difference. Low recycling <1 % can be obtained by adding gas guiding channels, while increasing mass recycling from 3 % to 8 % was achieved by adding annular tubes with careful control of differential pressure using pressure relief holes. Experimental cold-fuel-flow spray atomization quality was investigated using high-shutter-speed camera. Increasing palm oil flow from 60 ml/min to 120 ml/min significantly increased the spray angle from 1.8° to 21° while average droplet diameter reduced from 665 μm to 148 μm. Minimum CO emissions in the range of 132–135 ppm for diesel and biodiesel were achieved due to their better atomization compared to palm oil which resulted in slightly higher value of 207 ppm. The opposite effect was observed for NOx emissions where it elevated at the higher combustion temperature, where all the fuels showed comparable values in the range of 32–39 ppm. On the other hand, diesel suffered from its higher TIT value that reached 800 °C, compared to 785 °C and 762 °C for palm oil and biodiesel, respectively.